Tantangan dalam Pemanfaatan Interactive Flat Panel (IFP) pada Program Digitalisasi Pembelajaran di Kabupaten Banjar - Ulya Ulfah; Evarianty Masfini; Nuryadin Nuryadin (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study aims to analyze the challenges of utilizing Interactive Flat Panels (IFPs) in the learning digitization program in Banjar Regency. The study employs a quantitative descriptive approach using secondary data analysis sourced from the Ministry of Education and Culture’s Dapodik, the South Kalimantan BPMP Dashboard, and the Central Statistics Agency (BPS) for the years 2025–2026. The results indicate that IFP implementation still faces obstacles regarding internet infrastructure, teachers’ digital competencies, and the equitable distribution of devices. A total of 42.7% of schools have stable internet access, while 20.2% of schools do not yet have internet access. Additionally, only 37.8% of teachers have received adequate IFP training. This study emphasizes that the success of learning digitization is determined not only by the availability of technological devices but also by the readiness of infrastructure, human resource capacity, and support from a sustainable digital learning ecosystem in the region.